Risk Management in Micro Payment System in Emerging Economy: An Empirical Study From Ghana - Ackah, Owusu; Oteng, Emmanuel; Osei, Antwi John; Agyeiwaa, Doris (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2015)
This study examined the relationship between risk communication and review process and the entire risk management process in micro payment system. An empirical study was conducted into this phenomenon. Questionnaire was used to collect data from key informants within the micro payment industries. In all a total of 120 respondents was used. Furthermore, Pearson correlation and Linear regression analysis was conducted to test the hypotheses stated for this study. According to the statistical finding of this study is proved that information dissemination between providers and clients contributed significantly to risk mitigation and reduction. Also risk communication process coupled with a review process enabled firms to deal with ineffective strategies and practices.